Local Political Party and Ethnicity Influence on Acehnese Election - T.M Jamil; Irma Anggraini (Proceedings of AICS - Social Sciences, 2021)
This study focuses on “Local Political Party and Ethnicity Influence on Acehnese Election”. Theoretically, this study is expected to aid in the field of local politics, specifically elite politics and ethnicity. Through this study, the researchers are expected to broaden their education on the conceptual understanding of ethnicity. In the modern world, ethnicity is continually decreasing and replaced by social ethnicity based on economical class or other privileged groups. Through this study, the researchers observe the elitist behaviours that cause ethnicity and, theoretically, lead to thought discussion on the field of ethnicity, especially on the perspective of “instrumentalist/constructed ethnicity”. According to this perspective, ethnicity was constructed by a party. Ethnicity was formed due to local elite political parties spurring their followers, taking advantage of their primordial inheritance despite applying to a nationalist environment. To this end, the actors were put on a behavior of political perspective related to forming relations. This study was done to understand the action of political elites, especially on how they presented their ethnicity in their area of authority. The result of this study is expected to recommend the government to propose a non-discriminative public policy. The result of this study can also be utilized by elite political parties to show the appropriate process to manage ethnicity in a political party. There are two processes to disclose the meaning of ethnicity (1) understanding the point-of-view of the subjects, known as first-order understanding, and (2) evaluating the occurrences, known as second-order understanding. First-person understanding was done by analyzing the subjects of the study to obtain the correct understanding. The research would explore the incentive of the perpetrator of those actions. The obtained information is known as Bergerian understanding.Keywords: Local Political Party, Ethnicity, Local Election.